Pemberdayaan Masyarakat Melalui Badan Usaha Milik Desa Mangga Klonal 21 di Desa Oro-Oro Ombo Kulon Kecamatan Rembang Kabupaten Pasuruan. - Afifudin, Muhammad; Hardjati, Susi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Community empowerment is one of the steps that can be taken as an effort to improve community welfare, make the community independent and raise the dignity of the community. The same thing is done by BUMDes Mangga Klonal 21 by organizing a community empowerment program in the form of training and processing mango-based products. This research uses descriptive qualitative research. The theory used in this research is the theory of stages of community empowerment by the Delivery Team quoted by (Mardikanto & Soebiato, 2019), namely location selection, socialization of community empowerment, community empowerment process and also community self-reliance. The research results show that the community empowerment stages carried out by BUMDes Mangga Klonal 21 have gone well. It is proven that 3 of the 4 stages of empowerment have gone well, namely location selection, community empowerment outreach, community empowerment process. However, at the stage of self-reliance, society is still running quite well. This is proven by the fact that there are still a number of people who have not been able to run their businesses well and have been forced to close due to various factors, so community empowerment program organizers need to carry out more evaluations so that innovations emerge in further empowerment programs and also community empowerment program organizers need to carry out reviews regarding community businesses that are no longer running so that in the future no more community businesses will go bankrupt.